Hypoglycaemic Property of Nutraceuticals (Dhaka University Journal of Pharmaceutical Sciences, 2008)
Hypoglycemic property of four nutraceuticals named - black cumin, garlic, methi and karela has been investigated on an alloxan induced diabetic rat model. Glibenclamide was used as positive control and normal saline was used as negative control. Serum glucose levels of normal and diabetic induced rats were estimated by Glucose Oxidase method using a kit, and it were 4.33 ± 0.43 mmol/L and 8.27 ± 0.45mmol/L respectively. The alloxan induced diabetic rats were grouped into six, which were then treated with the four nutraceuticals and two controls. Treatment was given orally everyday for 28 days. Serum glucose level was analysed every 7 day intervals. It was observed that lowering of glucose level was significant (P = 0.01) for every 7 day treatment period. All of the nutraceuticals reduced the serum glucose level nearly to the normal value within 28 days. The rate of lowering of the glucose level was found to vary with the nutraceuticals. Garlic was found to be most active like the glibenclamide. The next active one was black cumin followed by methi and karela. The study conclude that nutraceuticals possess significant hypoglycemic property. Key words: Hypoglycaemia; Nutraceuticals; Black cumin; Garlic; Methi; Karela. Dhaka Univ. J. Pharm. Sci. 6(2): 105-107, 2007 (December)